Identifying “puff” characters in the figure-ground formation of the simulated patient’s visual experience - Maria Myron Charlotta Sengke; Paramita Atmodiwirjo; Yandi Andri Yatmo (Engineering and Applied Science Research, 2021)
This study addresses the limitation of patients’ visual experience in a healthcare environment. Clarity of visual experience occurs within the visual sphere that represents the seeing capacity defined by focus and peripheral view. The visual sphere is formed by the collections of “puff”- the unidentified parts as the components that create the wholeness of form in visual perception. This paper argues that the characters of puffs and their relationship could play an essential role in the formation of figure and ground. A simulation study was conducted by capturing the perceived scenes in a simulated patient room and then analyzing the character of regions in the scenes and their level of relationship. The study displayed the relationship between the region's position and the region's characters that form the integrity of the whole visual scenes. Knowledge of this relationship indicates that puff identification can be useful for evaluating the potential architecture elements within the visual capacity.